Evaluation of Dental Interns' Perception and Self-Confidence Levels Regarding Endodontic Treatment"- A Questionnaire Study - Shambhavi Gogia; Anushtha Jain; Laxmish Mallya; Ramya Shenoy; Swathi Pai (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the perception and self-confidence of Dental interns regarding endodontic treatment performed on patients. Material and Methods: A total of 111 dental interns from 5 different educational institutes of a state in South India participated in a questionnaire-based survey. The questionnaire consisted of 12 questions related to root canal procedures performed on patients. Analysis was done using SPSS version 17.0. Results: Sixty-five interns (59%) performed less than 10 root canal treatments on patients during the course of the internship. Twenty-eight interns (25% of the intern population) took up more than 10 root canal treatment cases, whereas only 18 interns (16%) did not perform the treatment on patients and answered the questionnaire based on their experience with extracted teeth model work. Only five interns out of 111 were 'Very confident' and 22 were 'Confident' in performing the root canal treatment. Conclusion: The present study indicates that the self-perceived confidence level among dental interns can affect their clinical performance. It also recommends additional hands-on workshops, problem-based learning and clinical guidance for the dental interns to become more confident with the root canal procedure.